Mathematical Phase Model of Neural Populations Interaction in Modulation of REM/NREM Sleep. Issue 6 (1st November 2016) - Acquistapace, Paolo; Candeloro, Anna P.; Georgiev, Vladimir; Manca, Maria L.
Abstract: Aim of the present study is to compare the synchronization of the classical Kuramoto system and the reaction - diffusion space time Landau - Ginzburg model, in order to describe the alternation of REM (rapid eye movement) and NREM (non-rapid eye movement) sleep across the night. These types of sleep are considered as produced by the cyclic oscillation of two neuronal populations that, alternatively, promote and inhibit the REM sleep. Even if experimental data will be necessary, a possible interpretation of the results has been proposed.